The Inflexible Structure of Global Supply Chains - Bayoumi, Tamim; Barkema, Jelle; Cerdeiro, Diego (Washington, D.C. : International Monetary Fund, 2019)
The rise of global supply chains has had profound effects on individual economies and the global trading system, thereby complicating standard macroeconomic analyses. For many of the new and challenging questions brought about by this phenomenon, such as its impact on the global business cycle and measurements of competitiveness, the answer largely depends on one specific aspect of global value chains: how easily they can re-configure in response to changes in prices. We propose a parsimonious, generalized specification to test the degree of global-supply-chain flexibility. Our estimates show that, in the short run, the production structure is highly inflexible, and that this rigidity has, if anything, risen over time as supply chains have deepened over time. This finding is robust to alternative price measures, including those that account for the U.S. dollar's outsized role in trade through invoicing. While in the long run all estimated elasticities rise, supply chains remain somewhat inflexible. Our results have implications for analyses of cross-country business-cycle dynamics, the propagation of sectoral shocks, and the measurement of international competitiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet